Vegetation Composition Drives The Hornbill Abundance in Tujuh Bukit Area, PT Bumi Suksesindo - Mukhlish Jamal Musa Holle; Fanny Sukma Sundari; Setiawan; Faisal Muslim; Dwi Karsono (Journal of Tropical Biodiversity, 2026)
Hornbills, keystone frugivores and bioindicators, reflect forest health. Their abundance depends on specific vegetation, like large cavity-bearing trees for nesting and diverse fruit-producing trees for foraging. In the southern Banyuwangi forests adjacent to mining areas, these characteristics may undergo changes due to operational activities that influence stand structure and the diversity of fruit-bearing trees, potentially affecting overall habitat suitability. A systematic investigation into vegetation composition and hornbill distribution is essential to establish baseline population data and inform targeted conservation strategies. We conducted hornbill and vegetation surveys in the areas adjacent to the mining site in the south of Banyuwangi Regency, East Java, Indonesia. Hornbill survey were conducted using a combination of line transect and point count methods. Vegetation analysis was conducted using plot-based sampling with 20 m x 20 m. All analyses were conducted in R with all visualisation made using package ggplot2. We found that despite of the patchy distribution, the abundance of three hornbill species, Anthracoceros albirostris, Buceros rhinoceros, and Rhyticeros undulatus, is similar across sites. Meanwhile, tree basal area, abundance, and composition differed across ecosystem types. Combining hornbill and tree data, we found that hornbill abundance is associated with tree composition and diversity, not overall plant abundance. To sum up, vegetation composition is a key determinant of hornbill abundance in tropical forests adjacent to mining sites. Therefore, conserving hornbills species requires preservation of the associated tree species providing food resources and nesting habitats.